Pendidikan Formal, Non Formal dan Informal dalam Desain Hadits Tarbawi - Kusmiran, Kusmiran; Husti, Ilyas; Nurhadi, Nurhadi (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2022)
This research is to find out formal, non-formal and informal education in Tarbawi Hadith design. This study used the library research method. The results showed that: 1) formal education includes: Islamic educational institutions, 2) Non-formal education includes: youth mosques, Al-Qur'an educational parks, dhikr or wiritan, yasinan, assemblies ta'lim, Islamic courses, Islamic boarding schools, life skills education, diniyah taklimiyah, youth education, vocational training centers, learning activity centers, and learning activity centers, and 3) Informal education includes: a). Increasing knowledge about Islamic morals, b). Exercise to do good things, c). Deep habituation grows and develops naturally in humans, and d). Growing and improving education.